Ultrasonic Tomography and Pulse Velocity for Nondestructive Testing of Concrete Structures - Varamashvili, Nodar D.; Asanidze, Bezhan Z.; Jakhutashvili, Mamuka N. (Journals of Georgian Geophysical Society, 2020)
The purpose of these research was to study the current state of the Tsageri catchment by geophysical methods. One such method is the ultrasound method. This method can measure and calculate the elastic parameters of the object of study without damaging it. We measured the propagation velocities of ultrasonic longitudinal (P) and shear waves (S) at the studied object. Then, material density (ρ), Poisson's ratio (ν) and Young's modulus (E) were calculated based on the measured speed. Ultrasonic devices, availability in our laboratory, can be used for the so-called tomography, "coverage" from the one side with the help of reflected waves. In this case, it is possible to identify voids of certain sizes, inhomogeneous regions in the body under study, and to distinguish regions of different densities (weakened).